2021
DOI: 10.1002/anie.202106713
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Tuning Local Environment of Hexagonal Boron Nitride for Oxidative Dehydrogenation of Propane

Abstract: Hexagonal boron nitride (h-BN) has lately received great attention in the oxidative dehydrogenation (ODH) reaction of propane to propylene for its extraordinary olefin selectivity in contrast to metal oxides. However, high crystallinity of commercial h-BN and elusive cognition of active sites hindered the enhancement of utilization efficiency. Herein, four kinds of plasmas (N 2 , O 2 , H 2 , Ar) were accordingly employed to regulate the local chemical environment of h-BN. N 2 -treated BN exhibited a remarkable… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
53
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 66 publications
(67 citation statements)
references
References 53 publications
(23 reference statements)
3
53
0
Order By: Relevance
“…Half-cell performances for the OER in acidic electrolytes were compared in Table S3 (ESI†) and the Pt embedded RuO 2 /C NRs showed better performances than those of other RuO 2 -based catalysts. The introduction of Pt and Co in the RuO 2 shell has led to a superior SA on PtCo–RuO 2 /C to that of Pt–RuO 2 /C likely due to the formation of defective RuO 2 structures 36 and electronic interaction between Pt and Ru.…”
Section: Resultsmentioning
confidence: 99%
“…Half-cell performances for the OER in acidic electrolytes were compared in Table S3 (ESI†) and the Pt embedded RuO 2 /C NRs showed better performances than those of other RuO 2 -based catalysts. The introduction of Pt and Co in the RuO 2 shell has led to a superior SA on PtCo–RuO 2 /C to that of Pt–RuO 2 /C likely due to the formation of defective RuO 2 structures 36 and electronic interaction between Pt and Ru.…”
Section: Resultsmentioning
confidence: 99%
“…The major band at 398.2 eV in N 1s XP spectra is the nitrogen bonded with boron in BN at the surface ( Figure 7 B). 11 A subpeak at 400.0 eV corresponds to N–H species, implying the formation of N defects, 9 and these N–H species maximize at spent 0.75V/BN-T ( Table S4 ). Recently, Lu et al have reported that these N defects might lead to the evolution of active BO x species.…”
Section: Results and Discussionmentioning
confidence: 99%
“… 3 , 8 Very recently, plasma treatment was reported to regulate the local environment of h-BN by creating nitrogen defects, favoring the generation of BO x active sites. 11 Efforts are also devoted to developing BO x -containing advanced materials for ODHP reaction, including boron phosphate 25 , 26 and metal–organic framework-derived catalysts. 27 …”
Section: Introductionmentioning
confidence: 99%
“…Consequently, a propane conversion of 26% and a propylene selectivity of 89.4% were achieved at 520 °C. 124 Crystallinity was found to be an important parameter for the h-BN performance and its higher degree enhanced O 2 binding. A selectivity of 82% at a conversion of 42% was obtained.…”
Section: Light Olefin Synthesis From Hydrocarbonsmentioning
confidence: 99%